THE INFLUENCE OF TEACHING METHODS AND LEARNING METHODS ON THE LEARNING OUTCOMES OF STIA NUSANTARA SAKTI SUNGAI PENUH STUDENTS: MEGAWATI - megawati (LPPM STIA Nusantara Sakti, 2022)
The learning outcomes obtained by students are influenced by many factors including the teaching methods of lecturers and student learning methods. This study aims to determine: 1) the influence of lecturer teaching methods and student learning methods on student learning outcomes at STIA Nusantara Sakti Sungai Full simultaneously and partially, 2) the influence of lecturer teaching methods and student learning methods on student learning outcomes at STIA Nusantara Sakti Sungai Penuh. simultaneously and partially, and 3) the variabels that most influence student learning outcomes at STIA Nusantara Sakti Sungai Penuh. The research approach used is a quantitative approach with a survey method. The respondents in this study were all students in the fifth semester of the 2021/2022 academic year, totaling 88 people. This study uses three variabels consisting of two independen variabels (lecturer's teaching method (X1) and student learning method (X2)) and one dependent variabel, namely student learning outcomes (Y). The data collection technique used is the questionnaire technique. The data analysis technique used is classical assumption test, multiple linear regression analysis, F test, t-test, coefficient of determination (KD), and effective contribution (SE). Based on the results of data analysis, the research results obtained are: 1). There is a significant effect between lecturer teaching methods and student learning methods on student learning outcomes simultaneously and partially, 2). Teaching methods and learning methods affect learning outcomes by 74,2%, and 3). The variabel that most influences learning outcomes is the lecturer's teaching method, which is 56,298%